ON GENERALIZATION OF THE THEOREM OF PICARD - Kamalian, H.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
The present article is devoted to the generalization of the classic theorem of Picard on entire functions in case of A-valued analitycal functions.